Constructing Community Understanding of the Synergy Between English and Technology for Work Readiness: A Qualitative Analysis: Penelitian - Mohammad Ilham Yasin; Iman Jauhari; Gigih Dwiananto; Maharani Dewi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The goal of this community service program is to increase public awareness of how digital technology and English language skills work together to prepare people for the workplace. The program employed a qualitative and community-based participatory method to provide interactive training, technology-mediated English practice, and mentoring activities that were based on actual workplace scenarios. In order to record participants' learning experiences and attitudes, data were gathered via observation, in-depth interviews, and focus group conversations. The results indicate that combining technology with English enhances participants' digital literacy, communication confidence, and knowledge of workplace expectations. The program also illustrates how experiential and participatory learning can effectively promote skill development and encourage ongoing education. In conclusion, this initiative emphasizes the significance of integrating language proficiency and technological proficiency in community service programs in order to increase employability and workforce flexibility.